A speckle-imaging search for close and very faint companions to the nearest and brightest Wolf–Rayet stars. Issue 2 (21st September 2021) - Shara, Michael M; Howell, Steve B; Furlan, Elise; Gnilka, Crystal L; Moffat, Anthony F J; Scott, Nicholas J; Zurek, David
ABSTRACT: Gravitationally bound companions to stars enable determinations of their masses, and offer clues to their formation, evolution, and dynamical histories. So motivated, we have carried out a speckle imaging survey of eight of the nearest and brightest Wolf–Rayet (WR) stars to directly measure the frequency of their resolvable companions, and to search for much fainter companions than hitherto possible. We found one new, close companion to each of WR 113, WR 115, and WR 120 in the separation range ∼0.2–1.2 arcsec 2 . Our results provide more evidence that similar-brightness, close companions to WR stars are common. More remarkably, they also demonstrate that the predicted, but much fainter and thus elusive companions to WR stars are now within reach of modern speckle cameras on 8-m class telescopes by finding the first example. The new companion to WR 113 is just 1.16 arcsec distant from it, and is ∼8 mag fainter than the WR star. The empirical probability of a chance line of sight of the faint companion at the position of WR 113 is <0.5 per cent, though we cannot yet prove or disprove if the two stars are gravitationally bound. If these three new detections are physical companions we suggest, based on their narrowband magnitudes, colours, reddenings, and GAIA distances that the companions to WR113, WR 115, and WR 120 are an F-type dwarf, an early B-type dwarf, and a WNE-type WR star, respectively.